Micro Credit and Women Empowerment: A Study in India - K. P. Saraswathy Amma K. S. M. Panicker M. Sumi (International Journal of Global Business, 1 (1), 184-213, December 2008, 2008)
Microfinance programs are important institutional devices for providing small credit to the rural poor in order to alleviate poverty. The strength of micro credit lies in its ability to organize idle women into a productive workforce with their proven creditworthiness. This paper puts forward how Micro Credit has received extensive recognition as a strategy for economic, social and personal empowerment of women and seeks to examine the impact of Micro Credit with respect to poverty alleviation of rural women. A study was conducted on the Kudumbasree project, a micro credit scheme in Palakkad district which is one of the backward districts of Kerala state in India. Women, who are targeted by Kudumbashree, find it an opportunity for `instant cultural International upward mobility'. The study showed that the micro credit scheme showed that income, savings, unity and freedom are the major benefits.